Hate Speech In Election 2019: Case Study Of Youth Organizations - Setiawandari, Harsih; Munandar, Adis Imam (Journal of Strategic and Global Studies, 2021)
Technology advance such as social media utilization to communicate, to express opinions, to interact with each other, and to discover and share information, but this also has its own susceptive. Its positive effect, social media can be used to accelerate the spreading of information, but the negative effects are the spreading of radical ideas, hate speech, hoaxes, etc. which can threaten the national defense and the sovereignty of the Republic of Indonesia. This research used complex models and a limited amount of samples so that in the data analysis using Smart-PLS software. Smart-PLS using the bootstrapping methods or random multiplication. The results of the research show that knowledge has a positive impact and significant to the attitude of PMII cadre towards hate speech in the 2019 presidential election with the value of P-Values1, 98 in the amount of 14,148. This result shows that the higher knowledge of the cadre about the hate speech in the presidential election 2019, the better attitude of PMII cadres to respond to hoaxes and hate speech in the presidential election 2019 to not make, spread, and affected by the hoaxes and hate speech